THE ROLE OF ISLAMIC EDUCATION IN PROMOTING WOMEN'S EMPOWERMENT - Suud Sarim Karimullah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
This study explores the critical role of Islamic education in promoting women's empowerment for a journey towards a more inclusive and equitable society. This study adopts the literature study method with a systematic and comprehensive approach to literature analysis in the search, collection, and evaluation of literature sources relevant to the topic of study. The study results stated that Islamic education supports gender equality and women's empowerment. By providing equal access to Islamic education, women can develop the skills, knowledge, and gender awareness necessary to play an active societal role. However, significant challenges need to be addressed, such as limited access, gender bias, patriarchal social norms, and financial problems. Nonetheless, with the shared commitment of governments, educational institutions, communities, and families, Islamic education can be a force that encourages women's empowerment and creates a more just, inclusive, and sustainable society. In addition, it is essential to continue to push for reforms in Islamic education, strengthen the role of women in society, and overcome the barriers that prevent women from reaching their full potential.